All-epiphyseal All-Inside Technique for Anterior Cruciate Ligament Reconstruction in Prepubescent Patient: A Case Report - Lumban Gaol, Imelda; Hernugrahanto, Kukuh Dwiputra; muslim, Jeffry andrianus; utomo, Dwikora novembri (Indonesian Hip and Knee Society (IHKS), 2023)
Anterior cruciate ligament injuries are common seen in active and young patients. The ACL reconstruction technique in skeletally immature patients tries to minimize the growth disturbance. All physeal sparing technique is technically demanding. In this paper, we described physeal sparing technique of ACL reconstruction in skeletally immature patient. This is an all-epiphyseal all-inside ACL reconstruction with retrodrill of the femoral and the tibial sockets. Both sockets are within epiphysis. This technique used free loop system. This free loop system allows us to make a socket with length 15 mm, that is safe from the physis. This socket also allows us to tension the graft adequately with minimum sockets length. We present a case of 16 years old male who underwent all-epiphyseal all inside reconstruction with our rehabilitation protocol.